TINGKAT MOTIVASI BERPRESTASI, MODALITAS BELAJAR, DAN TINGKAT LOCUS OF CONTROL MAHASISWA PRODI PGMI FAKULTAS TARBIYAH DAN KEGURUAN UIN SUNAN AMPEL SURABAYA - Sihabudin, Sihabudin (Journal Of Islamic Elementary School (JIES), 2018)
This study aims to investigate the level of achievement motivation, learning modalities and the level of locus of control of PGMI study program students at Tarbiyah and Teacher Training at Sunan Ampel UIN Surabaya. This type of research is survey research. Data collection uses documentation and questionnaire techniques. The data analysis technique uses Descriptive Statistical Analysis. The results of this research are: 1) There are 188 (89,5%) students of PGMI Department of Tarbiyah and Teaching Faculty of Sunan Ampel Islamic State University those who have high level of achievement motivation, 20 students (9,5%) those who have medium level of achievement motivation, and 2 students (1%) those who have low level of achievement motivation. 2) There are 108 (51,5%) students of PGMI Department of Tarbiyah and Teaching Faculty of Sunan Ampel Islamic State University those who have visual learning modality, 62 students (29,5%) those who have auditory learning modality, and 40 students (19%) those who have kinesthetic learning modality, 3) There are 4 (2%) students of PGMI Department of Tarbiyah and Teaching Faculty of Sunan Ampel Islamic State University those who have Very Internal Locus of Control, 184 students (88%) those who have Internal Locus of Control, 22 students (10%), those who have between internal and External Locus of Control, 0 students (0%) those who have External Locus of Control,and 0 students (0%) those who have Very External Locus of Control.